2017
DOI: 10.1002/per.2087
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Romantic Interest at Zero Acquaintance: Evidence of Sex Differences in Trait Perception but Not in Predictors of Interest

Abstract: We evaluated five competing hypotheses about what predicts romantic interest. Through a half-block quasi-experimental design, a large sample of young adults (i.e., responders; n = 335) viewed videos of opposite-sex persons (i.e., targets) talking about themselves and responders rated the targets’ traits and their romantic interest in the target. We tested whether similarity, dissimilarity, or overall trait levels on mate value, physical attractiveness, life history strategy, and the Big-Five personality factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 121 publications
1
30
0
Order By: Relevance
“…Most studies that investigated matching on physical attractiveness in initial romantic encounters, however, found no support for the Matching Hypothesis (e.g., Curran & Lippold, 1975; Eastwick & Finkel, 2008; Huston, 1973; Kurzban & Weeden, 2005; Lee et al, 2008;Olderbak et al, 2017; Walster et al, 1966; see also Kalick & Hamilton, 1986; Luo & Zhang, 2009; Taylor et al, 2011; Van Straaten et al, 2009).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies that investigated matching on physical attractiveness in initial romantic encounters, however, found no support for the Matching Hypothesis (e.g., Curran & Lippold, 1975; Eastwick & Finkel, 2008; Huston, 1973; Kurzban & Weeden, 2005; Lee et al, 2008;Olderbak et al, 2017; Walster et al, 1966; see also Kalick & Hamilton, 1986; Luo & Zhang, 2009; Taylor et al, 2011; Van Straaten et al, 2009).…”
mentioning
confidence: 99%
“…This Running head: MATE VALUE AND REAL-LIFE ROMANTIC ENCOUNTERS 7 supposition was proposed as a consequence of the findings from studies on physical attractiveness that did not find support for the Matching Hypothesis. Almost all of these studies instead found a positive main effect of a potential partner's physical attractiveness:The higher a potential partner's physical attractiveness, the higher were participants' romantic attraction, interest in another date, and likelihood of initiating contact with this potential partner (e.g., Berscheid et al, 1971; Curran & Lippold, 1975; Eastwick & Finkel, 2008; Fletcher, Kerr, Li, & Valentine, 2014; Hitsch, Hortaçsu, & Ariely, 2005; Huston, 1973; Kurzban & Weeden, 2005; Lee et al, 2008; Luo & Zhang, 2009;Olderbak et al, 2017; Stroebe, Insko, Thompson, & Layton, 1971; Walster et al, 1966; see also Asendorpf et al, 2011;Montoya, 2008). However, as deduced above, the crucial question is whether these findings also hold for global mate value.…”
mentioning
confidence: 99%
See 3 more Smart Citations